The Levels of Heavy Metals in the Soil of Illegal Open Dumpsites in Malaysia - Kuok Ho Daniel Tang; Zhu Hang Goh (Tecno Scientifica Publishing, 2022)
This study aims to understand the soil impacts of illegal dumpsites in Malaysia through quantifying the heavy metals in the soil of two dumpsites, one receiving construction waste and the other receiving municipal solid waste. Five soil samples were collected from each dumpsite, and sampling was repeated in the second week to examine the temporal changes in the levels of heavy metals. All sampling was conducted in triplicates. The soil samples were sieved, dried, and digested with aqua regia at 70 °C, after which the digested mixtures were filtered. The filtrates were diluted and tested with an atomic absorption spectrophotometer for heavy metals. The soil heavy metal concentration ranges were as follows: Al (24.67-142.20 mg/kg), Cd (< 0.01-0.083 mg/kg), Cu (0.10-14.99 mg/kg), Fe (11.20-241.77 mg/kg), Mn (0.09-22.60 mg/kg), Ni (0.02- 0.77 mg/kg), and Zn (0.14-35.03 mg/kg). All the heavy metals have been detected at all the sampling points except that the Cd levels at some sampling points were below the detection limit. The levels of heavy metals varied spatially and temporally, though higher Cd, Cu, Fe, Mn, Ni, and Zn were detected consistently at two sampling points of the dumpsite receiving municipal waste. This could be linked to the electrical and electronic waste at the dumpsite. The levels of heavy metals in the soil did not constitute soil contamination. However, it is important to control illegal dumping activities to reduce the associated health and safety concerns, such as infestation of vermin, fire, physical hazards, and odor.